Importance of radon studies in rural areas and correlation of indoor radon level with radon inventory. (2015) - Banerjee, Kailas Sekhar; Sengupta, Debashish
The measurement of indoor radon in villages is very important as 50% of the world populations live in villages, and rural houses normally have very low air exchange rates. This study has estimated the possible indoor radon level from five types of rocks, which are readily available to build houses in Eastern Singhbhum district of India. In the process to calculate this radon inventory, radium content and radon flux rate were measured in the selected rocks. Then calculated radon emanation factor was compared with the possible indoor radon concentration computed from the available air ventilation rate of typical Indian houses. It was found that granite generated low radon level and it can be a good alternative choice as building material instead of other regionally used rocks. This study also suggests that important geological parameters, which develop and increase porosity, can effectively increase radon inventory.